المتغيرات الاقتصادية العالمية المعاصرة وآثارها على الاقتصادات العربية - خضير ايمان عبد; حسين عيادة سعيد (Journal of Economics and Administrative Sciences, 2008)
The Arab economy suffers from many structural imbalances problems which are getting complicated by the appearance of the world economic variables. This change held risky challenges for the Arab economies in the light of unsuitable regional and international conditions. Since that it has been very essential for the Arab experts, especially those related to economy and politics, to face those new challenges or, at least, adapt with them believing that they can have both positive and negative impacts on the Arab economy. This study has acquired its importance in the light of the critical levels the Arab economy reached out of the world economic variables, resulting in long-term crises. Of the most fundamental variables, facing the Arab economy and the world as well are: • The scientific and technological revolution. • The increasing tendency towards creating world-wide economic groups. • Globalization and its instruments. Aiming to explain the world economic impacts on the Arab economies, the study is divided into three chapters. The first chapter deals with Arab economies and contemporary developments. It was discussed in terms of two sections: The current situation of the Arab economies, and the developments of the Arab contemporary economies. The second chapter reviews the world economic variables mentioned before. The last chapter discussed the economic impacts of the world economic variables on the Arab economies. At the end, the study reached to several conclusions and recommendation which might help doing something to the Arab economy as a whole.